2023
DOI: 10.1002/hbm.26314
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the acute effects of running on cerebral blood flow and food cue reactivity in healthy young men using functional magnetic resonance imaging

Abstract: Acute exercise suppresses appetite and alters food‐cue reactivity, but the extent exercise‐induced changes in cerebral blood flow (CBF) influences the blood‐oxygen‐level‐dependent (BOLD) signal during appetite‐related paradigms is not known. This study examined the impact of acute running on visual food‐cue reactivity and explored whether such responses are influenced by CBF variability. In a randomised crossover design, 23 men (mean ± SD: 24 ± 4 years, 22.9 ± 2.1 kg/m2) completed fMRI scans before and after 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
(100 reference statements)
1
5
2
Order By: Relevance
“…(58) Furthermore, a previous study conducted in young men showed lower reactivity to high-density energy foods than to low-density energy foods using blood oxygen level-dependent functional magnetic resonance imaging after acute high intensity exercise. (59) In the present study, there were significant differences in implicit wanting and the relative preference for taste appeal bias between the high and low GI trials. This result indicates that consuming a low GI meal may suppress the preference for sweet foods.…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…(58) Furthermore, a previous study conducted in young men showed lower reactivity to high-density energy foods than to low-density energy foods using blood oxygen level-dependent functional magnetic resonance imaging after acute high intensity exercise. (59) In the present study, there were significant differences in implicit wanting and the relative preference for taste appeal bias between the high and low GI trials. This result indicates that consuming a low GI meal may suppress the preference for sweet foods.…”
Section: Discussionsupporting
confidence: 38%
“…Several studies have reported that the hedonic system of non-homeostatic appetite control is affected by meal-induced changes in hormone concentrations, habitual physical activity, and structured exercise. (34,5659) A previous study suggested that insulin secretion decreases dopamine signalling, which could cause a decrease in the rewarding aspects of food. (34) Additionally, the stimulation of ghrelin has been reported to activate reward-related areas in the brain, such as the amygdala, ventral striatum, anterior insula, orbitofrontal cortex, and hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Such alteration is most notable in brain regions implicated involved reward processing and was further augmented after exercise, suggesting exercising could induce an altered anticipatory reward processing (Table 2 ) (Killgore et al ., 2013 ; Luo et al ., 2018 ). According to published research, subjects in good health who perform acute aerobic exercise for 60 minutes show decreased neural reactivity to high-calorie foods in the bilateral insula, OFC, and putamen, and increased neuronal reactivity in the left precuneus (Evero et al ., 2012 ; Thackray et al ., 2023 ). High-intensity exercise at 70% of maximum heart rate for 60 minutes decreases neuronal activity to pictures of high-calorie food in OFC and left HPC, as compared with non-foods.…”
Section: Exercise Influences Brain Healthmentioning
confidence: 99%
“…Various studies show that moderate exercise regimens induce acute improvements of positive affect, especially immediately after exercise (Reed and Ones, 2006 ). Moreover, there is some evidence that acute exercise can exert motivational effects (Bothe et al, 2013 ), including phenomena of transient appetite suppression or altered reactivity to food cues (Dorling et al, 2018 ; Dera et al, 2023 ; Thackray et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…But these methods provide no (or limited) information about region-specific effects, and there are theoretical accounts which assume that resource limitations may also necessitate temporary downregulation of brain metabolism in certain brain regions (e.g., the reticular-activating hypofrontality model: Dietrich and Audiffren, 2011 ). Indeed, preliminary evidence from magnetic resonance imaging (MRI) studies using arterial spin labeling (ASL) indicates post-exercise CBF increases in young adults for the hippocampus (Steventon et al, 2020 ) or posterior insula, but also concomitant CBF decreases in the medial orbitofrontal cortex and dorsal striatum (Thackray et al, 2023 ). Indirect evidence for region-specific activity changes also comes from resting-state functional MRI (rs-fMRI) studies.…”
Section: Introductionmentioning
confidence: 99%